2018
DOI: 10.1177/2372732218781643
|View full text |Cite
|
Sign up to set email alerts
|

Improving Medication Understanding and Adherence Using Principles of Memory and Metacognition

Abstract: More than half of older adults regularly take multiple medications. Rates of medication non-adherence are high, which undermines both patients’ health and the economy. Memory and metacognitive factors (such as misplaced confidence) help explain why patients across the lifespan may not understand or follow prescribed regimens. These factors include difficulties in remembering confusing information; patients’ and practitioners’ potential overconfidence in memory; and misunderstandings about memory. Patients, pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 92 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…In this study, non-adherence was observed in a majority of the participants (74, 62.71) with forgetfulness being the main culprit (64, 86.49%). As a lot of the patients were on polypharmacy, receiving excessive information on their medications may result in difficulties to retain vital information, thus leading to forgetfulness [ 31 ]. Medication adherence is only significantly correlated with race ( p = 0.011, r = −0.233).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, non-adherence was observed in a majority of the participants (74, 62.71) with forgetfulness being the main culprit (64, 86.49%). As a lot of the patients were on polypharmacy, receiving excessive information on their medications may result in difficulties to retain vital information, thus leading to forgetfulness [ 31 ]. Medication adherence is only significantly correlated with race ( p = 0.011, r = −0.233).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the people over the age of 65 should take five or more medications regularly for chronic diseases and more than half of these patients had complication to follow the recommendation of their physicians, leading to serious healthcare and economic consequences [ 6 ]. Symptoms of dementia make it even more difficult to take antidementia drugs appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, a short task reduced or eliminated the extent to which younger and older adult participants overestimated their own and some others' performance. Further research is needed to determine how to implement cognitive principles to enhance learning and perspective-taking when people encounter large amounts of (potentially confusing) medical information, such as at a doctor's office or when reading medication dosage instructions (see Hargis & Castel, 2018a, for a review). Perhaps incorporating established techniques to improve memory and metacognitive accuracy into medical communication (e.g., testing; Larsen, Butler, Lawson, & Roediger, 2013;Roediger & Karpicke, 2006; making important information salient; Castel, 2008;Hargis & Castel, 2018a;Hargis, Siegel, & Castel, 2019;Middlebrooks, McGillivray, Murayama, & Castel, 2015; or understanding overconfidence; Koriat & Bjork, 2005;Metcalfe, 1998) can lead to less confusion, better remembering, and improved health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to determine how to implement cognitive principles to enhance learning and perspective-taking when people encounter large amounts of (potentially confusing) medical information, such as at a doctor's office or when reading medication dosage instructions (see Hargis & Castel, 2018a, for a review). Perhaps incorporating established techniques to improve memory and metacognitive accuracy into medical communication (e.g., testing; Larsen, Butler, Lawson, & Roediger, 2013;Roediger & Karpicke, 2006; making important information salient; Castel, 2008;Hargis & Castel, 2018a;Hargis, Siegel, & Castel, 2019;Middlebrooks, McGillivray, Murayama, & Castel, 2015; or understanding overconfidence; Koriat & Bjork, 2005;Metcalfe, 1998) can lead to less confusion, better remembering, and improved health outcomes. In summary, the present work suggests that younger and older adults' perspective-taking can be improved after task experience, a finding which has implications for communicating and learning health-related information across the lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation